P170 Impact of high definition transcranial direct current stimulation over the dorsomedial prefrontal cortex on social cognition. Issue 3 (March 2017) - Martin, A.; Meinzer, M.
Abstract : Question: The dorsomedial prefrontal cortex (dmPFC) is considered a key component of the "social brain" and has been associated with self-other distinctions across a variety of "theory of mind" (ToM) tasks. Objective: To assess the impact of high-definition transcranial direct current stimulation (HD-tDCS) over the dmPFC on a low-level visual perspective taking task (VPT), high-level affective ToM task (Mind in the Eyes), and on the self-reference effect in episodic memory. Methods: Using a within-subjects, cross-over design, twenty healthy young subjects (18–35 yrs) received 1 mA excitatory (anodal) tDCS for 20 min or sham-tDCS whilst completing three socio-cognitive tasks. tDCS was administered using a one-channel DC-stimulator and two concentric round rubber electrodes. The Mind in the Eyes task (MITE) involved selecting the emotion or cognitive state represented in a set of eyes. The subjects were then asked how often they, or another (Barack Obama), felt that way. Age and gender judgements acted as a low-level social judgement control condition. After approximately 30 min, subjects were asked to recall as many chosen emotion/cognitive state words they could remember, followed by a recognition task. In between, subjects completed a task able to measure implicit, level-1 (line of sight judgment), and level-2 (location of objects relative to other's perspective) VPT. Results: There was no effect of anodal-tDCS on MITE performance. Anodal-tDCS increased the impact of the other agent's perspective during self-perspective judgements in level 1 and level 2 VPT, but not during implicit VPT. Specifically, during anodal-tDCS, there was a greater difference in reaction time between scenes congruent or incongruent with the perspective of the other agent. During the recognition memory task, anodal-tDCS increased memory for other-encoded emotion words with no impact on self-encoded emotion words. Conclusions: The findings demonstrate for the first time that high-definition tDCS over the dmPFC can improve social cognition, especially concerning the salience of other encoded memories or the perspective of others. This proof of concept study paves the way for assessing the impact of HD-tDCS in clinical populations who may benefit from improved social cognition.